2015
DOI: 10.1016/j.jnnms.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of combustion fronts in porous media

Abstract: We study a model for forward propagation of a combustion front through a porous medium. The reaction involves oxygen and a solid fuel. We assume that this solid fuel depends on the space variable. We also assume that the amount of gas produced by the reaction is equal to the amount of gas consumed by it. By actual solutions, we prove the existence and uniqueness of solution of the model. We show that temperature is non-decreasing function of time. We use the similarity variable to transform the system of parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…To examine the properties of the solution of the transient two-dimensional hydromagnetic flow over an impermeable surface with ohmic and viscous heat dissipation, we used the actual solution approach and method of upper and lower solution as presented in the work of Olayiwola (2011). The results obtained revealed that the fluid velocity…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the properties of the solution of the transient two-dimensional hydromagnetic flow over an impermeable surface with ohmic and viscous heat dissipation, we used the actual solution approach and method of upper and lower solution as presented in the work of Olayiwola (2011). The results obtained revealed that the fluid velocity…”
Section: Discussionmentioning
confidence: 99%
“…Definition 1 (Olayiwola, 2011): A smooth function is said to be a lower solution to the problem < = •./, 2, 3 Where: (Olayiwola, 2011): A smooth function is said to be an upper solution to the problem. < = •./, 2, 3 Where:…”
Section: Properties Of Solutionmentioning
confidence: 99%
“…However, the concept of performance that becomes the students' understanding is not changed. The presentation is in the form of demonstration media [8] by separating the ignition system from the more complex system. The other way to build understanding is teaching with visual media that is available in various online media.…”
Section: Ignition System Contact Breaker (Iscb) Electrical Partmentioning
confidence: 99%
“…Sayed-Ahmed et al [13] investigated time dependent pressure gradient effect on unsteady MHD Couette flow of an electrically conducting, viscous, incompressible fluid bounded by two parallel non-conducting porous plates with heat transfer under exponential decaying pressure gradient. Olayiwola [14] investigated the modeling and simulation of combustion fronts in porous media. Jana et al [15] examined Couette flow through a porous medium in a rotating system.…”
Section: Introductionmentioning
confidence: 99%